x | − | 2 | − | ( | 2 | − | x | ) | ÷ | 2 | = | ( | x | − | 2 | ) | ÷ | 3 |
Left side of the equation = | x | − | 2 | − | 2 | × | 1 2 | + | x | × | 1 2 |
= | x | − | 2 | − | 1 | + | x | × | 1 2 |
= | 3 2 | x | − | 3 |
3 2 | x | − | 3 | = | ( | x | − | 2 | ) | ÷ | 3 |
Right side of the equation = | x | × | 1 3 | − | 2 | × | 1 3 |
= | x | × | 1 3 | − | 2 3 |
3 2 | x | − | 3 | = | 1 3 | x | − | 2 3 |
3 2 | x | − | 1 3 | x | = | - | 2 3 | + | 3 |
7 6 | x | = | - | 2 3 | + | 3 |
7 6 | x | = | 7 3 |
x | = | 7 3 | ÷ | 7 6 |
= | 7 3 | × | 6 7 |
= | 1 | × | 2 |
x | = | 2 |